2007
DOI: 10.1111/j.1469-8137.2007.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among xylem transport, biomechanics and storage in stems and roots of nine Rhamnaceae species of the California chaparral

Abstract: Summary• Here, hypotheses about stem and root xylem structure and function were assessed by analyzing xylem in nine chaparral Rhamnaceae species.• Traits characterizing xylem transport efficiency and safety, mechanical strength and storage were analyzed using linear regression, principal components analysis and phylogenetic independent contrasts (PICs).• Stems showed a strong, positive correlation between xylem mechanical strength (xylem density and modulus of rupture) and xylem transport safety (resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
333
6
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(375 citation statements)
references
References 45 publications
28
333
6
8
Order By: Relevance
“…However, thick roots have low surface:volume ratio (SVR) and offer higher resistance to the radial flow of water, both causing lower root absorption potential (Larcher 1995;Huang and Eissenstat 2000). Furthermore, the abundance of xylem parenchyma is negatively correlated with the resistance to cavitation (Pratt et al 2007b). The existence of a trade-off between carbohydrate storage and drought tolerance in roots may contribute to explain the differences in below-ground structure between R+ and R-species.…”
Section: Discussionmentioning
confidence: 98%
“…However, thick roots have low surface:volume ratio (SVR) and offer higher resistance to the radial flow of water, both causing lower root absorption potential (Larcher 1995;Huang and Eissenstat 2000). Furthermore, the abundance of xylem parenchyma is negatively correlated with the resistance to cavitation (Pratt et al 2007b). The existence of a trade-off between carbohydrate storage and drought tolerance in roots may contribute to explain the differences in below-ground structure between R+ and R-species.…”
Section: Discussionmentioning
confidence: 98%
“…Low wood density species show, therefore, a faster height growth (Muller-Landau 2004;Poorter 2008;King et al 2005) and a low wood density is therefore especially advantageous for light-demanding species that need to monopolize gaps by growing rapidly in height and complete their life cycle before they are being overtopped by competing neighbouring plants. Wood density is emerging as a core functional trait (Chave et al 2009), not only because of its importance for tree stability and architecture (King et al 2006) but also because of its importance for defence against pathogens (Loehle 1988), stem hydraulics and cavitation resistance (Pratt et al 2007;Markesteijn et al 2011), and hence, photosynthetic carbon gain (Santiago et al 2004). The effect of wood density was largely maintained in the ANCOVA analysis, suggesting that wood density may contribute to architectural variation not only between families but also within families.…”
Section: Wood Densitymentioning
confidence: 99%
“…Drought adapted plants have a greater resistance to cavitation, 19,20 which appears related to an increased relative thickness of the conduit or the fibre cell walls, 5,21 and so an increased wood density. 5,22 However, since the mechanical properties are determined by the micro fibril angle (MFA) of the S2 cell wall layer as well as density, 23 the data from the few studies measuring the mechanical effects of hydraulic adaptation have not found consistent effects.…”
mentioning
confidence: 99%
“…5,22 However, since the mechanical properties are determined by the micro fibril angle (MFA) of the S2 cell wall layer as well as density, 23 the data from the few studies measuring the mechanical effects of hydraulic adaptation have not found consistent effects. 24,25 In these studies, complex natural systems were investigated making it difficult to distinguish between various climatic effects. We therefore grew seedlings from the three tree species Ochroma lagopus, Acacia karroo and Betula pendula under well-watered and droughted conditions, respectively, and measured the effect on the modulus of elasticity, the yield stress and the density (unpublished results).…”
mentioning
confidence: 99%